The Use of Personal Protective Equipment (PPE) in Maternal Care During the COVID-19 Pandemic - Mawarni, Devina Bunga; Ekawati, Fitriana Murriya; Putri, Likke Prawidya; Bismantara, Haryo (Faculty of Medicine, Public Health, and Nursing, 2024)
Introduction: The COVID-19 pandemic has driven rapid changes in healthcare delivery worldwide, including maternal care. In Indonesia, there has been an increase in maternal and infant mortality during the COVID-19 pandemic. Hospitals and health centers are high-risk locations for the transmission of this disease. Controlling potential hazards in healthcare facilities can be achieved by using Personal Protective Equipment (PPE). However, there has been an increased demand for PPE during the pandemic, leading to a shortage of availability. Nevertheless, PPE is a crucial component for protecting both healthcare staff and patients from COVID-19 transmission. Research related to the evaluation of PPE usage among healthcare workers during the COVID-19 pandemic, especially in maternal healthcare, is limited. Therefore, this study aims to evaluate the use of Personal Protective Equipment (PPE) by healthcare workers when providing maternal care in healthcare facilities in the city of Banjar, West Java. Methods: This research is a quantitative study in the form of a descriptive cross-sectional study. The minimum sample size consisted of 96 individuals, including general practitioners, midwives, nurses, and obstetricians who are currently actively providing maternal care services in healthcare facilities in the City of Banjar. Data collection was conducted using the snowball sampling method in February – March 2022, with the El-Sokkary questionnaire from 2021 as the modified instrument distributed online. Result: The research results showed that the majority of respondents were female (96,3%), worked as midwives (95,4%), were aged 25-34 years (40,3%), had 6-10 years of work experience (29,3%), and in the past two weeks, the majority worked in primary care settings (40,3%). Exposure to training and guidelines, as well as exposure to COVID-19 patients, were both considered high (grand mean 2,7 and 2,2). Healthcare facility policies indicated that the majority did not impose sanctions (75,2%) if personal protective equipment (PPE) was not used according to guidelines, and the compliance rate ranged from 65-80% (43,1%). The frequency of PPE usage was categorized as high (grand mean 3,6), with only 58,7% feeling that the availability of PPE was sufficient, with N95 masks and similar items experiencing the most shortages (73,3%). Healthcare workers' negligence was relatively low (grand mean 2,9), but the compliance with PPE usage guidelines varied from 0 to 42,8%, depending on the type of service provided. Conclusion: The types of personal protective equipment (PPE) frequently used by healthcare professionals (midwives, nurses, general practitioners, and obstetricians) include surgical masks/N95 masks, waterproof surgical gowns, face shields, goggles, headgear, protective shoes, aprons, and gloves. The overall compliance rate for the use of PPE is approximately 65-80% according to local healthcare facility regulations. The evaluation of PPE usage indicates that the compliance with PPE usage among maternal healthcare providers varies depending on the type of service provided, with the highest compliance observed in the case of delivery services for suspected/confirmed COVID-19 patients. The results of this research are expected to be considered by healthcare facilities and relevant stakeholders in documenting and providing the necessary types of PPE required by healthcare professionals in their daily practice.